Evaluating the diagnostic significance of the R2* value on 3.0T MRI for assessing the severity of warm hepatic ischemia-reperfusion injury - Shichao Xu; Qian Ji; Jing Xu (BMC Gastroenterology)
Abstract Background Magnetic resonance imaging (MRI) may be a non-invasive tool for managing warm hepatic ischemia-reperfusion injury (WHIRI). Purpose We aimed to evaluate the diagnostic utility of the R2* values derived from 3.0T blood oxygen level-dependent (BOLD) MRI in assessing the severity of WHIRI. Methods Fifty healthy adult New Zealand white rabbits were randomly divided into 5 groups with 10 rabbits in each. The experimental groups (40 rabbits) underwent clamping of the hepatic artery and the portal vein for 10, 20, 30, or 40 min, followed by 6 h of reperfusion to induce WHIRI. The other 10 rabbits comprised the normal control group. All animals were underwent conventional 3.0 T and BOLD MRI. Animals were euthanized and the serum levels of biochemical indicators were determined. Correlations between R2* values, biochemical indicators, and WHIRI staging were assessed using Spearman’s rank correlation coefficient. The diagnostic efficacy of R2* values was evaluated using ROC curves. Results R2* values increased gradually with prolonged warm ischemia with significant differences across groups (F = 133.25, P < 0.05). A strong positive correlation was detected between R2* values and WHIRI staging (r = 0.878, P = 0.000). Biochemical indicators (ALT, AST, LDH, MDA, and MPO) increased significantly, while SOD levels decreased with prolonged warm ischemia (P < 0.05). R2* values exhibited a strong positive correlation with biochemical indicators (r > 0.495) and a negative correlation with SOD levels (r=-0.658). The diagnostic efficacy of the R2* values was highest for predicting WHIRI above stage S4 (AUC = 1.000). Conclusion R2* values on BOLD MRI provide a sensitive and accurate method for assessing WHIRI. The diagnostic efficacy of the R2* values was the best for predicting WHIRI above stage S4.